Global Simulation of Insect Meat Production Under Climate Change - Mulia, Randy Nathaniel; Doi, Hideyuki (Frontiers in Sustainable Food Systems, 2019)
The world's population could exceed nine billion by 2050, putting future global food security at risk. To fulfill the increased food demand, food production should be increased. However, with limited land use, current livestock production is not sustainable. To tackle this problem, insect meat can be used as an alternative to conventional livestock. With its high nutritional component and a low land use area, insect has many potentials. However, it is largely unknown how much land can be saved if we replace current conventional livestock with insects, especially under different climate change scenarios. Here, we examine the land use effectiveness of raising insects as food, together with using other conventional meat sources under different climate scenarios outlined in the Special Report on Emissions Scenarios (A1, A2, B1, B2). Then, the current livestock meat ratio is analyzed to examine the readiness of each country to fulfill its needs. We also simulated land use changes with different proportions of insect meat production. Based on the land use simulation in different SRES scenarios, insect meat would be effective in fulfilling animal-based energy demands. We statistically examined the relationship of livestock land ratio with countries' variables (GDP, population, forest area, protected area, government efficiency). Based on an analysis involving the use of various meat composition policies in the four SRES scenarios, insect meat with its high efficiency of land use can be more effective in fulfilling animal-based energy demands than other livestock types. However, to achieve food security in the future, it is a necessity that insect meat be used alongside other alternative solutions that are suitable to each country/area.